Chemical oxygen demand and tannin/lignin removal from paper mill wastewater by electrocoagulation combined with peroxide and hypochlorite treatments - Caglak, Abdulkadir; Sari-Erkan, Hanife; Engin, Guleda Onkal (TAYLOR & FRANCIS LTD, 2024)
The present investigation sought to assess the practicality of utilizing a combined pre-treatment approach comprising electrocoagulation, peroxide, and hypochlorite treatments for the removal of chemical oxygen demand (COD) and tannin/lignin from paper mill wastewater. The study aimed to optimize the operating parameters with a view to maximizing the removal efficiencies while minimizing energy consumption. A pair of iron electrodes were used as anode and cathode in the study, and the main operating parameters were determined as initial pH, applied current, treatment time and oxidant dosage/COD ratio. Response surface methodology (RSM) was used to evaluate the effect of these parameters on COD and tannin/lignin removals. The primary findings of the investigation indicated that the integration of electrocoagulation with peroxide and hypochlorite treatments exhibited efficacy in removing COD, tannin/lignin, colour, phenol, and turbidity from paper mill wastewater. The optimized conditions resulted in COD removal efficiencies of 48.13 +/- 2.2% and 29.53 +/- 1.4% for EC with H2O2 and Ca(OCl)(2), respectively. Tannin/lignin removal efficiencies were 92.59 +/- 3.6% and 94.09 +/- 1.8% for EC-H2O2 and EC-Ca(OCl)(2), respectively. The specific energy consumption (SEC) values showed that EC-Ca(OCl)(2) required 7 times more energy than EC-H2O2 for removing 1 kg COD. The principal deduction drawn from the study was that EC-H2O2 pre-treatment demonstrated superior COD removal efficiency and lower energy consumption, while EC-Ca(OCl)(2) pre-treatment exhibited greater efficiency in removing toxic and recalcitrant pollutants. In future studies, it would be useful to conduct research to increase COD removal efficiency in addition to tannin/lignin removal in EC-Ca(OCl)(2) process.
Keywords: Paper mill wastewater; tannin; lignin removal; electrocoagulation; oxidation; RSM; optimization; ELECTRO-FENTON; SODIUM-HYPOCHLORITE; PHOTO-FENTON; KRAFT PULP; TECHNOLOGY; INDUSTRY; COLOR; DECOLORIZATION; Environmental Sciences & Ecology